(untitled) (Journal of Economic Research & Business Administration, 2015)
In the article it is considered the basic directions developing human capital of the Republic of Kazakhstan on the basis of research results devoted to the country’s competitiveness and factors forming the national human capital, according to the state programs of the Republic of Kazakhstan. It is especially underlined the significance of education, particularly higher one, and innovation potential of the country which substantially increase the level of competitiveness of the national economy and ensure sustainable national development.